2000
DOI: 10.1007/s003600000137
|View full text |Cite
|
Sign up to set email alerts
|

The absorption of calcium ions from the ovine reticulo-rumen

Abstract: Net Ca2+ and Mg2+ absorption rates were measured in vivo from buffer solutions placed in the washed reticulo-rumen, isolated in situ in 30 conscious, trained sheep. An increase in concentration of short chain fatty acids (SCFA) in the buffer, over the range 0-50 mM, was shown to stimulate the net rates of absorption of Ca2+ and Mg2+ ions from the rumen. Similarly, the results of in vitro experiments, carried out with ovine rumen epithelium mounted in short-circuited Ussing chambers, showed that the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…When Ca 21 intake rises to 8 g/day in sheep or to 120 g/day in cattle, absorption of Ca 21 is shifted to preintestinal regions (Grace et al, 1974;Khorasani et al, 1997;Schrö der and Breves, 2006 (Hö ller et al, 1988a and1988b;Schrö der et al, 1997;Wadhwa and Care, 2000). Active ruminal Ca 21 absorption can be increased by concentrate feeding (Uppal et al, 2003), in the presence of SCFAs (Schrö der et al, 1997 andWadhwa and Care, 2000;Uppal et al, 2003, LeonhardMarek et al, 2007a or by increasing the amounts of luminal chloride (Leonhard-Marek et al, 2007a), whereas sulfate ions seem to have stimulatory and depressing effects with no net change of Ca flux rates in vitro (Leonhard-Marek et al, 2007b). An increased absorption of undissociated SCFA will provide protons to the cell interior, while the ruminal uptake of SCFA 2 or Cl 2 via anion exchange mechansims is accompanied by a secretion of bicarbonate (Gä bel et al, 1991a) and an increase in surface pH (Leonhard-Marek et al, 2006).…”
Section: Absorption Of Calciummentioning
confidence: 99%
“…When Ca 21 intake rises to 8 g/day in sheep or to 120 g/day in cattle, absorption of Ca 21 is shifted to preintestinal regions (Grace et al, 1974;Khorasani et al, 1997;Schrö der and Breves, 2006 (Hö ller et al, 1988a and1988b;Schrö der et al, 1997;Wadhwa and Care, 2000). Active ruminal Ca 21 absorption can be increased by concentrate feeding (Uppal et al, 2003), in the presence of SCFAs (Schrö der et al, 1997 andWadhwa and Care, 2000;Uppal et al, 2003, LeonhardMarek et al, 2007a or by increasing the amounts of luminal chloride (Leonhard-Marek et al, 2007a), whereas sulfate ions seem to have stimulatory and depressing effects with no net change of Ca flux rates in vitro (Leonhard-Marek et al, 2007b). An increased absorption of undissociated SCFA will provide protons to the cell interior, while the ruminal uptake of SCFA 2 or Cl 2 via anion exchange mechansims is accompanied by a secretion of bicarbonate (Gä bel et al, 1991a) and an increase in surface pH (Leonhard-Marek et al, 2006).…”
Section: Absorption Of Calciummentioning
confidence: 99%
“…The potential role of the reticulorumen has also been examined by applying the washed rumen technique and a positive correlation between ruminal Ca concentration and Ca net absorption could be demonstrated (Höller et al, 1988). Active mechanisms have been shown to make significant contributions to Ca transport in caprine as well as ovine rumen, by measuring Ca flux rates in Ussing chambers (Schröder et al, 1997(Schröder et al, , 1999Wadhwa and Care, 2000;Uppal et al, 2003). These mechanisms could only be detected when short chain fatty acids (SCFAs) were present in the luminal buffer solutions.…”
Section: Sheep and Goatsmentioning
confidence: 99%
“…Furthermore, the significant net flux rates of Ca were recently reported in the caprine duodenum and jejunum and in the ovine jejunum using the Ussing chamber technique [33]. In addition, it has been recently reported that there existed significant net Ca absorption in the rumen, and this is increased by 1,25 (OH) 2 D 3 and short-chain fatty acids (SCFAs) [5,38]. On the contrary, it has been believed that the rumen is the major site of Mg absorption in the ruminant.…”
Section: Dietary Magnesium Increases Calcium Absorption Of Ovine Smalmentioning
confidence: 99%
“…Martens et al reported that the mechanism of net Mg absorption in the rumen is dependent on the transepithelial potential difference by the difference of K concentration between mucosal and serosal [25,26]. Also, it was recently reported the net Mg absorption was influenced by CO 2 , SCFAs and phosphate in the rumen [12,38].…”
Section: Dietary Magnesium Increases Calcium Absorption Of Ovine Smalmentioning
confidence: 99%